2018
DOI: 10.1038/s41380-018-0198-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific impact of prenatal androgens on social brain default mode subsystems

Abstract: Early-onset neurodevelopmental conditions (e.g., autism) affect males more frequently than females. Androgens may play a role in this male-bias by sex-differentially impacting early prenatal brain development, particularly neural circuits that later develop specialized roles in social cognition. Here, we find that increasing prenatal testosterone in humans is associated with later reduction of functional connectivity between social brain default mode (DMN) subsystems in adolescent males, but has no effect in f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 78 publications
3
49
0
Order By: Relevance
“…These results are not only compatible with the in-silico predictions and the in-vivo mouse rsfMRI data presented here, but is also compatible with several prior lines of work. Our prior work highlighted that DMN functional connectivity in adolescent males, but not females, is affected by heightened levels of fetal testosterone and this network was heavily comprised of MPFC and PCC 13 . In the same work, we showed that a cortical midline DMN subsystem comprising MPFC and PCC highly expresses several genes relevant for excitatory postsynaptic potentials (e.g., MEF2C, GRIK2, GRIA1, SCN3A, SCN9A, NPTX2).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…These results are not only compatible with the in-silico predictions and the in-vivo mouse rsfMRI data presented here, but is also compatible with several prior lines of work. Our prior work highlighted that DMN functional connectivity in adolescent males, but not females, is affected by heightened levels of fetal testosterone and this network was heavily comprised of MPFC and PCC 13 . In the same work, we showed that a cortical midline DMN subsystem comprising MPFC and PCC highly expresses several genes relevant for excitatory postsynaptic potentials (e.g., MEF2C, GRIK2, GRIA1, SCN3A, SCN9A, NPTX2).…”
Section: Discussionmentioning
confidence: 97%
“…In the same work, we showed that a cortical midline DMN subsystem comprising MPFC and PCC highly expresses several genes relevant for excitatory postsynaptic potentials (e.g., MEF2C, GRIK2, GRIA1, SCN3A, SCN9A, NPTX2). Importantly, the expression of these genes in human neuronal stem cells are elevated after exposure to the potent androgen DHT 13 . Thus, one potential explanation for the male-specific reduction of H in vMPFC could have to do with early developmental and androgen-sensitive upregulation of genes that play central roles in excitatory postsynaptic potentials, and thus ultimately affecting downstream E:I imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations